SEX CHROMATIN FREQUENCY IN BUCCAL MUCOSA CELLS AMONG BENGALEE HINDU FEMALES OF WEST BENGAL, INDIA (Zdravstveni glasnik, 2024)
INTRODUCTION: Quantitative determination of sex chromatin in cell nuclei has been demonstrated an associationbetween the prevalence of sex chromatin and hormonal levels of female reproductive cycles.OBJECTIVE: The objective of the present study was to understand the prevalence of sex chromatin among different hormonedependent reproductive stages of Bengalee Hindu caste females living in West Bengal, India.SUBJECTS AND METHODS: Buccal smear samples were collected from 500 apparently healthy female participants categorizedinto 5 different reproductive stages of pre-menarche, menarche, pregnancy, lactation, and menopause. 100 cellsfrom each individual and 100 participants from each group have been studied at random.RESULTS: The result revealed a differential prevalence of sex chromatin among the participants at different reproductivestages (ranges 60). The mean prevalence of sex chromatin was highest among lactating mothers (59. 22±4. 06) andlowest among pre-menarcheal females (14. 09±3. 34). Mean difference among all reproductive stages was found significant(p